Real Dynamics and Bifurcation of the Family - Salma Faris (Al-Rafidain Journal of Computer Sciences and Mathematics)
The purpose of this work is to study the dynamics of the family of nonlinear functions ={ It is shown that the bifurcation in the dynamics of   occurs at the critical parameter value